Vertical distribution and sources of perylene in miocene mudstones from the northeastern Bengal Basin of Bangladesh - Hossain, HMZ (Bangladesh Journal of Scientific and Industrial Research, 2014)
The distributions and sources of perylene (Pery) and penta-aromatic hydrocarbons were investigated in 10 Miocene mudstones from the NE Bengal Basin, Bangladesh using gas chromatography-mass spectrometry (GC-MS). Pery concentrations were high in most of the samples, and highest levels were found in samples of strong terrigenous influence of organic matter deposited under reducing environmental conditions. Mudstones in the Bokabil Formation (upper Surma Group) contain relatively high abundances of benzofluoranthenes (Bflas), benzo[e]pyrene (BePy) and benzo[a]pyrene (BaPy) attributed to their combustion origin. Pery to pentacyclic aromatic isomers (PAIs) ratios implies an influence of diagenetic sources, whereas low BaPy/BePy ratios indicate that these compounds were originated from combustion sources. Wood degrading fungi in arid to humid and seasonal climatic conditions was also the possible source of Pery in the studied succession. DOI: http://dx.doi.org/10.3329/bjsir.v48i4.18275 Bangladesh J. Sci. Ind. Res. 48(4), 257-264, 2013